Mongolia’s state policy in the field of mongolistics - Grayvoronsky, Vladimir V. (The New Research of Tuva, 2012)
Article reviews the contemporary policy of Mongolia in the state field of mongolistics basing on analysis of the official documents, personal observations, author’s participation in Russian-Mongolian cooperation.